Subject-specific finite element analysis to characterize the influence of geometry and material properties in Achilles tendon rupture - Shim, Vickie B.; Fernandez, Justin W.; Gamage, Prasad B.; Regnery, Camille; Smith, David W.; Gardiner, Bruce S.; Lloyd, David G.; Besier, Thor F. (Journal of biomechanics, 2014)
Achilles tendon injuries including rupture are one of the most frequent musculoskeletal injuries, but the mechanisms for these injuries are still not fully understood. Previous in vivo and experimental studies suggest that tendon rupture mainly occurs in the tendon mid-section and predominantly more in men than women due to reasons yet to be identified. Therefore we aimed to investigate possible mechanisms for tendon rupture using finite element (FE) analysis. Specifically, we have developed a framework for generating subject-specific FE models of human Achilles tendon. A total of ten 3D FE models of human Achilles tendon were generated. Subject-specific geometries were obtained using ultrasound images and a mesh morphing technique called Free Form Deformation. Tendon material properties were obtained by performing material optimization that compared and minimized difference in uniaxial tension experimental results with model predictions. Our results showed that both tendon geometry and material properties are highly subject-specific. This subject-specificity was also evident in our rupture predictions as the locations and loads of tendon ruptures were different in all specimens tested. A parametric study was performed to characterize the influence of geometries and material properties on tendon rupture. Our results showed that tendon rupture locations were dependent largely on geometry while rupture loads were more influenced by tendon material properties. Future work will investigate the role of microstructural properties of the tissue on tendon rupture and degeneration by using advanced material descriptions.